Heterobimetallic Mg–Ag coordination polymer with luminescence and 2, 4, 6-Trinitrophenol sensing properties. (8th January 2018) - Yin, Xiulian; Meng, Suci; Xie, Jimin
Graphical abstract: The first SCN-bridged Mg–Ag heterobimetallic coordination polymer with strong emission was developed as the highly sensitive 2, 4, 6-Trinitrophenol sensor. Abstract: The first SCN-bridged Mg–Ag coordination polymer, namely [Mg(DMF)4 Ag2 (SCN)4 ] n (1 ) (DMF = N, N-dimethylformamide) has been synthesized and structurally characterized by FT-IR spectroscopy, elemental analysis and single crystal X-ray diffractions. X-ray structural analysis reveals that1 displays a two-dimensional (2-D) framework, which contains Mg metallic atoms, Ag2 dimeric units, and SCN − bridges with two kinds of connected manners. This Mg–Ag coordination polymer exhibits strong luminescence property and can act as highly sensitive sensor for 2, 4, 6-Trinitrophenol in both DMF and aqueous media. Moreover, the mechanism of1 for highly sensitive detection of TNP had been preliminarily studied.